Selected grammatical categories in the Czech language as understood by non-Czech speaking students - Žvaková, Kateřina (Bohemistyka, 2023)
Teaching elementary Czech to university students is a challenging task. Given the profound complexity and numerous exceptions found in the Czech language system, a balance between oversimplification on the one hand and overwhelming students on the other hand needs to be sought. The objective of this study is to find out whether and to what extent do beginner Czech learners understand how selected grammatical categories work in Czech. The results imply that more attention should be paid to word formation processes as insufficient understanding of them was identified not only in students who were new to Czech but also in the control group.